1993
DOI: 10.1007/bf01974349
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 1-methyl-tetrahydro-Β-carboline-3-carboxylic acid in blood and organs of rat. A possible causative substance of eosinophilia-myalgia syndrome associated with ingestion ofl-tryptophan

Abstract: 1-Methyl-tetrahydro-beta-carboline-3-carboxylic acid (MTCA) may cause eosinophilia-myalgia syndrome (EMS) associated with ingestion of L-tryptophan. The distribution and excretion of MTCA were studied in rats which had received perorally a single 1.6 mg/kg dose of MTCA. MTCA concentrations in blood, kidney, liver, brain, heart, spleen, lung and gastrocnemius muscle were measured by HPLC combined with fluorometric detection. The concentration of MTCA in each organ reached a maximum at 1 h and then gradually dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Nevertheless, it has been reported that THbCs might be absorbed and accumulated in tissues. [31] Then, dietary sources rich in THbCs likely contribute to increase the amount of these compounds occurring in biological tissues and fluids, [2] where they might have a significant contribution by acting as radical scavengers. Foods containing high level of these compounds such as soy sauces and seasoning, wines, vinegars and fruit products (juices, jams, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been reported that THbCs might be absorbed and accumulated in tissues. [31] Then, dietary sources rich in THbCs likely contribute to increase the amount of these compounds occurring in biological tissues and fluids, [2] where they might have a significant contribution by acting as radical scavengers. Foods containing high level of these compounds such as soy sauces and seasoning, wines, vinegars and fruit products (juices, jams, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the diet along with a possible accumulation could explain their presence in tissues and biological¯uids. In this regard, experiments in rats have shown absorption and accumulation of TH C-3-COOHs in organs (Ogawa et al 1993). Although some research has already been accomplished on the biological signi® cance of TH Cs and Cs, further additional work is needed for its complete elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…␤-Carbolines formed between hexulose, xylose, furan-2-carboxaldehyde, acetaldehyde, and glucose on the one hand and amino acids such as lysine, glycine, proline, arginine, histidine, and tryptophan on the other have been reported (5)(6)(7)(8)(9)(10). They are formed endogenously in plants and animals (for example, harmane, structure I in Fig.…”
mentioning
confidence: 99%
“…On the other hand, there have been reports (14 -16) that some of these Maillard products are antioxidative in nature. ␤-Carbolines are found ubiquitously in a variety of foods: grain flour, soy sauce and soy protein, milk, beer, and wine, and perhaps as a consequence, in animal fluids and tissues such as blood, milk, urine, kidney, liver, and brain (10,17). Several reports have appeared in recent literature of the presence of ␤-carbolines in human tissues.…”
mentioning
confidence: 99%